Odpowiedź :
a)
[tex] \frac{3}{5} + \frac{10}{11} = \frac{33}{55} + \frac{50}{55} = \frac{83}{55} = 1 \frac{28}{55} [/tex]
b)
[tex] \frac{2}{3} \times \frac{9}{8} = \frac{1}{1} \times \frac{3}{4} = \frac{3}{4} [/tex]
c)
[tex]5 \times \frac{3}{4} = \frac{15}{4} = 3 \frac{3}{4} [/tex]
d)
[tex] \frac{3}{7} \times \frac{10}{11} = \frac{30}{77} [/tex]
e)
[tex] \frac{2}{3} \times \frac{9}{8} = \frac{1}{1} \times \frac{3}{4} = \frac{3}{4} [/tex]
f)
[tex]6 \times \frac{5}{2} = 3 \times 5 = 15[/tex]
g)
[tex]2 \frac{1}{2} \times \frac{1}{3} = \frac{5}{2} \times \frac{1}{3} = \frac{5}{6} [/tex]
h)
[tex]1 \frac{1}{5} \times 2 \frac{1}{2} = \frac{6}{5} \times \frac{5}{2} = \frac{3}{1} \times \frac{1}{1} = 3[/tex]
i)
[tex] \frac{2}{3} + \frac{3}{5} = \frac{10}{15} + \frac{9}{15} = \frac{19}{15} = 1 \frac{4}{15} [/tex]
j)
[tex]2 \frac{1}{4} + 1 \frac{3}{6} = 2 \frac{3}{12} + 1 \frac{6}{12} = 3 \frac{ 9 }{12} = 3 \frac{3}{4} [/tex]
k)
[tex]5 - \frac{2}{3} = 4 \frac{1}{3} [/tex]
l)
[tex]2 \frac{1}{3} - \frac{2}{3} = 1 \frac{4}{3} - \frac{2}{3} = 1 \frac{2}{3} [/tex]
m)
[tex]7 \frac{1}{2} - 2 \frac{4}{5} = 7 \frac{5}{10} - 2 \frac{8}{10} = 6 \frac{15}{10} - 2 \frac{8}{10} = 4 \frac{7}{10} [/tex]
n)
[tex]1 \frac{2}{3} \times 2 \frac{3}{5} = \frac{5}{3} \times \frac{13}{5} = \frac{1}{3} \times \frac{13}{1} = \frac{13}{3} = 4 \frac{1}{3} [/tex]
o)
[tex]3 \frac{1}{2} \div 1 \frac{1}{5} = \frac{7}{2} \div \frac{6}{5} = \frac{7}{2} \times \frac{5}{6} = \frac{35}{12} = 2 \frac{11}{12} [/tex]
Myślę że pomogłem ;)